PENGARUH FAKTOR MOTIVASI TERHADAP PRESTASI KERJA PEGAWAI BAGIAN KEUANGAN SEKRETARIAT DAERAH KOTA SAMARINDA - Nuuridha Matiin (Politeknik Negeri Samarinda, 2021)
This research was conducted with the aim to determine the work motivation of employees of the Finance Section of the Samarinda Regional Secretariat and to see the variables that affect the performance of employees in carrying out their daily duties. This study was conducted on 31 respondents from the population of employees who were the object of research by distributing questionnaires to respondents at the Finance Section of the Daearah Secretariat of Samarinda City.The variables studied were all independent variable factors (X) that affect employee motivation, consisting of; Physiological needs (X1), security (X2), social needs (X3), appreciation (X4), and self-actualization (X5), while the dependent variable is work performance (Y). The research method used for data analysis is descriptive quantitative method through multiple linear regression models assisted by SPSS software.The results of the analysis of this study concluded that; Simultaneously the independent variables consisting of: physiological needs (X1), security (X2), social needs (X3), appreciation (X4), and self-actualization (X5) proved to have a significant effect on employee motivation. Partially, the security variable is a variable that has a dominant influence on the work performance of the Finance Section of the Regional Secretariat of Samarinda.